Organizational strategic marketing management: Critical analysis of the marketing strategies / practices currently employed by the Water Resources Commission, Ghana, indicating challenges and opportunities. - Kwadade-Cudjoe, Francis (Archives of Business Research, 2021)
Strategic marketing management is the implementation of an organization’s marketing mission through focused processes to get the most out of existing marketing plan and to identify target customers. Again, it is to help the discovery of other marketing opportunities for the organization to transform plans into reality. The marketing plan should outline the marketing strategy of the organization for the coming year, quarter or month. A typical business marketing plan should include: overview of the marketing and advertising goals, description of the current marketing position, timeline of when tasks within the strategy will be completed, key performance indicators to be tracked, and description of the target market and customer needs. When an organization adopts this approach to market its products / services to customers / consumers, there is a strong expectation of success for the organization. The initial capital outlay pumped into businesses is normally huge, and this should not be made to go waste. However, most organizations gloss over this important point and put out mediocre plans and strategies to managing their businesses. Business wo/men should project their businesses from a better marketing angle with good competitive strategy to enable them achieve competitive advantage.